2018
DOI: 10.1253/circj.cj-17-0660
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Elevated Echocardiographic Index of Left Ventricular Filling Pressure and Acute Kidney Injury After Off-Pump Coronary Artery Surgery

Abstract: and mortality. 4,9 Hemodynamic disturbance during OPCAB has been reported to have a biventricular contribution, and the major cause is believed to be diastolic dysfunction and abnormal filling of both ventricles. 10,11 As such, it is possible that an underlying increased LVFP may aggravate the intraoperative hemodynamic disturbance, resulting in a higher rate of postoperative AKI. Although previous studies have reported the effect of diastolic dysfunction on postoperative outcomes, including death or major adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…In our study, the incidence of AKI was significantly higher in patients with an elevated postoperative E/e 0 after matching. A previous study showed similar results in patients who underwent off-pump coronary artery bypass with preserved preoperative LVEF [4]. The association between the elevated LVFP and postoperative AKI can be explained by the following mechanisms.…”
Section: Commentsupporting
confidence: 63%
See 2 more Smart Citations
“…In our study, the incidence of AKI was significantly higher in patients with an elevated postoperative E/e 0 after matching. A previous study showed similar results in patients who underwent off-pump coronary artery bypass with preserved preoperative LVEF [4]. The association between the elevated LVFP and postoperative AKI can be explained by the following mechanisms.…”
Section: Commentsupporting
confidence: 63%
“…Previous studies indicated the prognostic value of the preoperative E/e 0 ratio. The preoperative E/e 0 ratio was associated with postoperative complications, including AKI and major adverse cardiac events [1,2,4,21]. A composite of in-hospital cardiovascular complications, including embolic infarct, cardiopulmonary resuscitation, and requirement for cardioversion or pacemaker implantation, develops more frequently in patients with a preoperative E/e 0 ratio >12 than in those with an E/e 0 ratio 12 after isolated aortic valve replacement [2].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of previous studies, data related to demographic or perioperative variables known to be related to postoperative renal dysfunction were collected ( Table 1 ) [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 ]. The following perioperative clinical variables were collected: patient demographics, medical history, medication history, baseline laboratory finding, surgery type, operation time, type of anesthesia, intraoperative fluid and colloid administration, intraoperative transfusion amount, and intraoperative hemodynamic variables.…”
Section: Methodsmentioning
confidence: 99%
“…The result is an increase in renal venous and intra-abdominal pressure, which worsens renal function [30,31]. A higher E/e’ ratio is an independent predictor of AKI occurring after cardiac surgery [32,33]. An E/e’ ratio > 15 is associated with AKI among patients with ST-segment elevation myocardial infarction [34].…”
Section: Discussionmentioning
confidence: 99%